Electro-remediation of Chromium and Associated Heavy Metals from Soils Affected by Leather Tannery Waste Effluents in Sambrial Town, Pakistan - Maria Khalid; Sajid Rasheed Ahmad; Riffat Mahmood Qureshi; Naseer Ahmed; Sheeraz Mehboob; Syed Zahid Hussain; Muhammad Iqbal (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
A locally fabricated electrokinetic remediation apparatus was used for laboratory scale electrokinetic remediation of aqueous phase Cr and associated metals in coarse silty clay soil affected by waste effluents released from leather tanning factory located in Sambrial Town (Punjab), Pakistan. Acetic acid (0.1 M CH3COOH: pH = 3.9 and EC = 0.4 mS/cm at the start of the experiment) was applied as electrolyte for electrokinetic washing of aqueous phase Cr and associated metal species in field collected test soil contained in an electrolytic soil cell by applying a constant 30 V DC (equivalent to 1 V cm-1) across the cell for a period of 216 hours (~9 days). The pH and electrical conductivity of electrolytes (catholyte and anolyte) were measured at different time intervals during the course of electro-remediation. Contents of metals like Cr, Fe, Ni, Zn, Mn, Co, Pb and Sr in the test soil and aliquots of anolyte/catholyte were determined by the ICP-OES technique. Morphological changes in the test soil were observed through scanning electron microscope in response to electrokinetic washing of the soil. It is observed that after electro-remediation soil samples show that particles segregate and surface becomes more porous. It is noted that initially pH varies and then becomes constant, whereas electrical conductivity increases with time.